SONGS FROM YOUTUBE AS AN ALTERNATIVE MEDIA INNOVATION FOR TEACHING AND LEARNING ENGLISH - Asmi Rusmanayanti (Getsempena English Education Journal, 2019)
Since English is not our language, some EFL students often face difficulties in learning it. Therefore, the teachers try to create or adapt several techniques and try to find an alternative media for teaching English that can be used to solve the problem. Anyway, songs from YouTube are one of the alternative media in learning English. Through songs you can make the boredom away, can also have some fun while you are studying. Qualitative method was employed in this research. The data needed in this research were collected by using open-ended questionnaire and interview related to the songs from YouTube as a media innovation in learning English. The method used in this research is random sampling and chosen them as the representative of English Department of Lambung Mangkurat University academic year 2015 to 2017 which 40 students had involved during the research. The data analyzed based on the questionnaire and interview, all of the students mentioned that they love studying English through songs with a variation, not only seriously focused on grammar. They learnt many new words either the meaning or the way of pronouncing the words in the songs. From the selected songs on YouTube application, they just realized that songs can be used to learn grammar as well. In addition, the importance of through knowledge of English Language is becoming more and more obvious in modern world in which communication increasingly takes place in English.